The black book of quantum chromodynamics : a primer for the LHC era - Campbell, John, 1973-; Huston, Joey; Krauss, Frank (Oxford University Press, 2018)
This title provides an in-depth introduction to the particle physics of current and future experiments at particle accelerators. The text provides the reader with an overview of practically all aspects of the strong interaction necessary to understand and appreciate modern particle phenomenology at the energy frontier.